2021
DOI: 10.3389/fped.2021.635503
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Outcomes in Children Born Extremely and Very Preterm at 11 Years of Age

Abstract: Background: There is increasing evidence of prematurity being a risk factor for long-term respiratory outcomes regardless the presence of bronchopulmonary dysplasia (BPD).Aim: To assess the effect of prematurity on respiratory outcomes in children born ≤32 weeks of gestational age at 11 years of age.Materials and Methods: Fifty five ex-preterm children (≤ 32 weeks of gestational age), born in Chieti between January 1, 2006 and December 31, 2007, performed lung function and diffusing capacity test (DLCO) at 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…After finding that in confounder model breastfeeding duration was associated with FEV 1 z-score, FEV 1 /FVC z-score and FEF 75 % z-score, but not with DLCO z-score, we specifically investigated if the association between gestational age at birth and DLCO z-score, already described previously ( 13 ), could be explained by the mediating role of breastfeeding. We illustrated the mediation analysis in the Figure 2 .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…After finding that in confounder model breastfeeding duration was associated with FEV 1 z-score, FEV 1 /FVC z-score and FEF 75 % z-score, but not with DLCO z-score, we specifically investigated if the association between gestational age at birth and DLCO z-score, already described previously ( 13 ), could be explained by the mediating role of breastfeeding. We illustrated the mediation analysis in the Figure 2 .…”
Section: Resultsmentioning
confidence: 98%
“…In Italy, the Italian Health Institute report 11/44, including 3,235 preterm newborns from 56 Neonatal Intensive Care Units, confirmed that exclusively breastfeeding depended on the gestational age ( 12 ). In addition, in our previous study ( 13 ) we showed lower lung diffusing capacity (DLCO) z-score levels in ex-preterm children compared to children born at term later in childhood. Therefore, the relationship between breastfeeding and respiratory outcomes is more difficult to investigate in preterm infants than healthy controls.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations